Intellectual Property: Legal Provisions and Legal Cases in Nepal - Rashesh Vaidya (Studies in Law and Justice, 2023)
Strengthening the legal protection of intellectual property (IP) is a major concern for entrepreneurs, inventors, and intellectual communities. It is accountable to the nation to protect its indigenous technology by strengthening its legal footing. Nepal, being a member of the World Trade Organization, is bound to develop a legal framework for the protection of intellectual property. Hence, the country has updated the laws related to IP within the Constitution, Acts, and Rules. There are an increasing number of legal conflicts arising regarding intellectual property in the courts of Nepal. The paper deals with the decisions forwarded on IP-related cases by the Supreme Court of Nepal. In the context of Nepal, an issue or complaint related to IP is initially filed at the Department of Industry as per the prevailing legal provisions relevant to IP. If the settlement is not confined to the department, then the case is forwarded to the District Court. The district-level court settled most IP-related legal cases in Nepal. Further, if the district-level court does not settle the case, it is then appealed to the High Court (then the Appellate Court). Few IP-related legal cases have reached the jurisdiction of Nepal’s Supreme Court, where they have been quashed on appeal, upheld lower-level court judgments, or even upheld or defended the decision of the Department of Industry or the Copyright Registrar’s Office. Nevertheless, given the dynamic nature of the business environment, the court of law should also go for amicus curiae for a better understanding of the crimes and to give a proper judgment on IP-related cases. At the same time, the government of Nepal needs to enact the necessary acts to show a commitment to the promise made in an international arena like the World Trade Organization.